Sleep and bipolar disorder - Michel Bourin (Archives of Depression and Anxiety - Peertechz Publications, 2023)
A growing international scientific literature demonstrates the existence of sleep abnormalities and sleep/wake (or circadian) rhythms in bipolar disorder. These abnormalities exist during the acute phases of the disease, with the classic presentation of insomnia or hypersomnia during depressive episodes and a reduced need for sleep without feeling tired during manic episodes. But these disturbances can also appear or persist during phases of mood stability. However, it has now been clearly demonstrated that these disturbances can precipitate a new depressive or manic episode.